The future of lidar in planetary science - Cremons, Daniel R. (Frontiers in Remote Sensing, 2022)
Lidar has enabled advances in the knowledge of the solar system through geophysical and atmospheric studies of the Moon, Mercury, Mars, and several asteroids. The technique will continue to be used to obtain high-precision topographic data from orbit, but new techniques on the horizon are suited to uniquely address fundamental planetary science questions related to the evolution of airless bodies, volatile delivery and sequestration, atmospheric transport, and small body formation and evolution. This perspective highlights the history of lidar in planetary science and identifies several measurement approaches that may be adopted in the coming years.